FORMULASI PAKAN IKAN NILA (Oreochromis SP.) MANDIRI BERBAHAN BAKU LOKAL DI PAKWALI DESA BAKALAN KECAMATAN PURWOSARI KABUPATEN PASURUAN - Putrawan, Rio Agus; ikerismawati, senja; Sholiha, Illiyatus; Ernawati, Ernawati (Lempuk: Jurnal Ilmu Kelautan dan Perikanan, 2025)
Fish feed is an important thing in producing maximum products in fish farming activities. This research has been carried out which aims to provide independent tilapia (Oreochromis sp.) feed made from local raw materials using Pearson's Square calculations based on the parameters of protein content, fat content and crude fiber content. This research used a quantitative descriptive method, analyzing the quality of fish feed with the parameters of protein content, fat content and crude fiber content carried out at the Animal Medicine and Feed Testing Laboratory of the Animal Husbandry and Animal Health Service, Veterinary Center, Semarang, Central Java. This research was carried out from February to July 2024. The results of this research are the correct composition of raw materials in preparing a 2 kg fish feed formulation, namely 0.64 kg fish meal, 0.36 kg rice waste, 0.36 kg bread waste, dregs know 0.64 kg. The quality of independent tilapia feed (Oreochromis sp.) is made from local raw materials for tilapia during the rearing period with test parameters for protein 18.06% (minimum 25%), fat 4.415% (minimum 5%), and crude fiber 11.47% (maximum 8%) which means the feed does not meet the requirements of SNI 7242:2018 artificial feed for tilapia (Oreochromis sp)..